Selected Early Western Contributors to the Study of the Korean Language - Paweł Kida (Politeja)
The purpose of this article is to present Western scholars, five Christian missionaries and two diplomats, who contributed to the development of the study of Korean language and its rules of grammar. This examination includes a comprehensive analysis and description of works published at that time by John Ross (1877, 1882), Félix-Clair Ridel (1881), James Scott (1887, 1893), Camille Imbault-Huart (1893), Horace Grant Underwood (1890, 1914), James Scarth Gale (1894, 1903), and Annie Laurie Baird (1911), with a particular focus on their missionary or official foreign service activities, linguistic practices, grammatical content, and the language of translation from Korean into a native language. These works played an essential role in the formation of further linguistic research in Korea.